Identifying factors associated with increased rate of mortality of COVID-19 patients among Jordanian population: A multicenter case-controlled retrospective study - Al-Qerem, Walid; Safar, Mohammad; Safar, Ibrahim; Al-Ibadah, Mahmood (Jordan Journal of Pharmaceutical Sciences, 2023)
Coronavirus 2019 (Covid-19) is a serious infectious disease that affects humans globally. Identifying factors that increase the prevalence of mortality are of interest for the healthcare providers. Therefore, the present study aimed to evaluate many risk factors and its association with mortality among COVID-19 patients. A total of 353 patients enrolled in this multicentered case-controlled retrospective study that was conducted in two designated hospitals in Amman, Jordan on patients admitted between 25 October 2020 to 26 September 2021. According to a stepwise binary logistic regression analysis found that patients who took Meropenem (p<0.001) and beta blockers (p=0.004) had lower incidence to be discharge during hospitalization. Also, diabetic patients (p<0.001) had lower discharge rate. We concluded that patients with secondary bacterial infection during the course of hospitalization, patients who needed to take beta blockers and diabetic patients are at higher risk of mortality.